2016
DOI: 10.1021/acs.jafc.6b04074
|View full text |Cite
|
Sign up to set email alerts
|

Hydroxycinnamoyl Glucose and Tartrate Esters and Their Role in the Formation of Ethylphenols in Wine

Abstract: Synthesized p-coumaroyl and feruloyl l-tartrate esters were submitted to Brettanomyces bruxellensis strains AWRI 1499, AWRI 1608, and AWRI 1613 to assess their role as precursors to ethylphenols in wine. No evolution of ethylphenols was observed. Additionally, p-coumaroyl and feruloyl glucose were synthesized and submitted to B. bruxellensis AWRI 1499, which yielded both 4-ethylphenol and 4-ethylguaiacol. Unexpected chemical transformations of the hydroxycinnamoyl glucose esters during preparation were investi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 55 publications
0
10
0
Order By: Relevance
“…The mechanics of MS/MS enables analysis of intact glycosides without pre‐enzymatic treatment or acid hydrolysis, because the on‐line collision‐induced dissociation procedure can cause cleavage of (most likely) the glycosidic bond or other weak bonds within the compound to produce unique product ions for each analyte to allow identification and quantification. We found that ESI was more suitable as an ion source for the nine analyzed glycosides, than the APCI used in previous studies . MS parameters were ameliorated for each analyte, and all analytes exhibited higher precursor ion signal intensities and better fragmentation patterns in positive mode.…”
Section: Resultsmentioning
confidence: 76%
See 1 more Smart Citation
“…The mechanics of MS/MS enables analysis of intact glycosides without pre‐enzymatic treatment or acid hydrolysis, because the on‐line collision‐induced dissociation procedure can cause cleavage of (most likely) the glycosidic bond or other weak bonds within the compound to produce unique product ions for each analyte to allow identification and quantification. We found that ESI was more suitable as an ion source for the nine analyzed glycosides, than the APCI used in previous studies . MS parameters were ameliorated for each analyte, and all analytes exhibited higher precursor ion signal intensities and better fragmentation patterns in positive mode.…”
Section: Resultsmentioning
confidence: 76%
“…For instance, Pang et al has applied both neutral loss scan and multiple reaction monitoring (MRM) scan of LC-MS/MS for the identification and quantification of four regular glycosides (scopoletin, rutin, kaempferol, and quercetin, all commercially available for use as standards) in tobacco leaves [18]. Some wine industry-related studies have combined LC-MS and MS/MS with a stable isotope tracer technique to analyze guaiacol glycoconjugates in smoke-affected grapes [19][20][21][22]. Nevertheless, due to the difficulty in obtaining authentic standards for these compounds, little work has been done on the absolute quantitative analysis of glycosides in biological materials.…”
Section: Introductionmentioning
confidence: 99%
“…In grape juices those hydroxycinnamic acids are esterified, mainly to tartaric acid, in concentrations higher than 10 mg/L. In wines they may be present in the free or esterified form, either with tartaric acid [16,17], ethanol [18], hexoses [16] or polyphenols [7]. The release of hydroxycinnamic acids from anthocyanin esters during wine maturation may be only due to chemical reactions [7] but conversions of hydroxycinnamic acid precursors to VPs are typically dependent on enzyme or microbial activity.…”
Section: Volatile Phenols (Vps): Their Incidence and Originmentioning
confidence: 99%
“…In grapes or grape juices, the tartaric esters may be hydrolyzed by enzymes from contaminant fungi or from commercial pectolytic preparations, both with cinnamoyl decarboxylase activity, which releases free hydroxycinnamic acid forms [11]. Ethyl and glucose esters of hydroxycinnamic acids may be metabolized by Brettanomyces [16,18] contrarily to tartaric acid esters [16,17]. Most of these tartaric esters are hydrolyzed only after malolactic fermentation, and it has been hypothesized that the hydrolytic activity of the lactic acid bacteria follows the completion of malic conversion to lactic acid [19,20].…”
Section: Volatile Phenols (Vps): Their Incidence and Originmentioning
confidence: 99%
“…PAD and VPR activities are variable among the strains and principally modulated by the nature and concentration of the substrate (Barthelmebs et al, 2000; Silva et al, 2011; Filannino et al, 2015; Rosimin and Kim, 2015; Sturm et al, 2015; Cappello et al, 2016). Some B. bruxellensis strains have been observed to directly produce ethylphenols from p -coumaroyl glucose, feruloyl glucose and ethyl coumarate, but not from p -coumaroyl and feruloyl L -tartrate esters (coutaric and fertaric acids) (Hixson et al, 2012, 2016).…”
Section: Introductionmentioning
confidence: 99%